The Policy on Illegal Oil Palm Plantation Reform in Forest Area during Jokowi’s Presidency - Albertus Sentot Sudarwanto; Lego Karjoko; I Gusti Ayu Ketut Rachmi Handayani; Arifin Ma’aruf; Henning Glaser (Hasanuddin Law Review, 2022)
Indonesia is the largest oil palm producer. The area of oil palm plantations is approximately 3.4 million. However, this large potential is not part away from legal issues such as illegal oil palm plantations. It is also implied by overlapping regulations and permits. This study aims to examine the policy of illegal oil palm plantations reform and the rooted regulation problem in forest areas during Joko Widodo era. This research relies on a normative legal approach. Data was collected through the investigation of legal material regarding oil palm policies. The results of this study indicate that the overlapping regulation contributes negatively to the reformation attempt. Yet, there are no legal products and policies regarding the dispute settlement of illegal oil palm in forest areas. Repressive implementation of criminal law does not solve the problem at the grassroots. The establishment of Job Creation Law provides new hope for the settlement of oil palm plantations problem by mainstreaming the nonlitigation mechanism, namely administrative sanctions.